METODE PEMBELAJARAN TILAWATIL QURAN DALAM MENINGKATKAN SENI MEMBACA AL QURAN DI PESANTREN ASSA’ADATUL ISKANDARI PURWAKARTA - Iis Kustiani; Sanusi Uwes; Imam Tabroni (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The background of the problem is the low interest of students in qiroatil Quran lessons at the Assa'adatul Iskandari Islamic Boarding School, Purwakarta, West Java. Students feel that they do not have a good voice, are not confident, are not talented, have low interest in Qori / ah. The purpose of the study was to find out how the implementation, supporting and inhibiting factors, evaluation and application of the Qur'an qiroatil learning method in improving the art of reading the Qur'an. The research method used was descriptive with a qualitative approach. through interviews, observations and documentation studies, data comes from interview scripts, field notes, photos, videos, tapes, personal documents, notes or memos, and other official documents through primary and secondary data. The results of the research are described in a narrative manner. The results of the study applied the Idzhar, Idghom, Iqlab tajwid learning. Ikhfa and Qolqalah. Al Quran learning method used is Qiroati method, Hifzil Quran recitation (THQ) and Quran recitation. The Quran rhythm (Qiroatil) used is Bayyati, Hijaz, Shoba, Rost rhythms. Jiharkah, Sika, Nihawand. Assessment of 105 students who got good scores above the average 24 people. It is expected that students practice the Qur'an, increase Islamic faith, piety and apply the application of the Qur'an qiroatil learning method in improving the art of reading the Qur'an properly and correctly.